COMPARATIVE ANALYSIS OF COMPANY PERFORMANCE BEFORE AND AFTER MERGERS AND ACQUISITIONS IN COMPANY LISTED ON IDX 2018-2021 - Edrick, Jon; Wijaya, Andi (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to examine how companies trading on the Indonesia Stock Exchange fared before and after M&A deals were made in the years 2018 through 2021. In this Study, we employed a comparable quantitative approach called "purposive sampling" to collect our data. There are seven suitable businesses to use as examples. Descriptive statistics, a normality test, and the Wilcoxon signed-rank test were employed to analyze the data. There was no discernible change in the financial performance of companies listed on the Indonesia Stock Exchange (IDX) before and after the announcement of mergers and acquisitions, as measured by three financial ratios: return on assets (ROA), return on equity (ROE), and debt to equity ratio (DER), for the period of 2018-2021. Several elements, according to the findings of this research, determine the ultimate fate of mergers and acquisitions. Investors should be aware that mergers and acquisitions do not always improve business efficiency.